Studies of Moisture Absorption and Release Behaviour of Akund Fiber - Xue Yang; Liqian Huang; Longdi Cheng; Jianyong Yu (Advances in Mechanical Engineering, 2012)
Akund fiber is a new type of natural cellulose fiber. Because of its excellent properties, akund fiber has become one of the new ecological materials which have huge development potential. Recently natural fibers have shown great promise in a variety of applications that were previously dominated by synthetic fibers due to their important aspects of biocompatibility, possible biodegradation, nontoxicity, and abundance. Moisture absorption and release behaviour of natural fiber plastic composites is one major concern in their outdoor applications. So the knowledge of the moisture content and the moisture absorption and release rate is very much essential for the application of akund fiber as an excellent reinforcement in polymers. An effort has been made to study the moisture absorption and release behaviour of akund fiber and the mechanical performance of it at relative air humidity from 0% to 100%. The gain and loss in moisture content in akund fiber due to water absorption and release were measured as a function of exposure time under the environment, in which temperature is 20°C and humidity is 65%. The regression equations of the absorption and release process were established.